Quality of life disparities among Mexican people with systemic lupus erythematosus. - Ana Laura Hernández-Ledesma; Domingo Martínez; Elizabeth Fajardo-Brigido; Talía V Román-López; Karen J Nuñez-Reza; Andrea Y Tapia-Atilano; Sandra V Vera Del Valle; Donají Domínguez-Zúñiga; Lizbet Tinajero-Nieto; Angélica Peña-Ayala; Estefania Torres-Valdez; Gabriel Frontana-Vázquez; et al. (PLOS Digital Health)
Higher prevalence and worst outcome have been reported among people with systemic lupus erythematosus with non-European ancestries, with both genetic and socioeconomic variables as contributing factors. In Mexico, studies assessing the inequities related to quality of life for Systemic Lupus Erythematosus patients remain sparse. This study aims to assess the inequities related to quality of life in a cohort of Mexican people with SLE. This study included 942 individuals with SLE from the Mexican Lupus Registry (LupusRGMX) and two healthy control groups. Self-answered surveys were collected via the Research Electronic Data Capture platform between May 2021 and January 2023. Data was analyzed as a cross-sectional study. A random forest model was implemented to assess potential predictive variables. Permutation tests were performed to analyze the effect health providers had on diagnosis lag and quality of life's differences among socioeconomic levels. Partial correlation analysis between the number of patients and rheumatologists registered was also performed. Systemic Lupus Erythematosus participants had significantly lower quality of life than healthy people (p-values < 0.0001). Socioeconomic status, delay in diagnosis, and corticosteroid consumption were the factors that influenced QoL the most (RMSE = 9.53 with the importance variable validated); lower quality of life was associated with lower socioeconomic status (p-value < 0.0001). Disparities in health services were reflected in longer diagnosis time among people with public health providers (p-value = 0.0419). A significant association between diagnosed patients and available rheumatologists by geographical state was observed (ρ = 0.4, p-value = 0.0259), which can be translated into restricted access to specialists. Since most of our cohort exhibited low socioeconomic status, it is important to consider them as a vulnerable population; this study settles the necessity to deepen the effects of the socioeconomic disparities, allowing to design public policies and strategies aimed to reduce Systemic Lupus Erythematosus disparities, therefore improving quality of life of Mexican people with Systemic Lupus Erythematosus.